Serbian nation and its problems from the perspective of Polish nationalists in the early 21st century = Naród serbski i jego problemy z perspektywy polskich nacjonalistów na początku XXI wieku - Sokół, Jakub (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article analyzes the situation of Serbs in Kosovo in terms of its reception by contemporary Polish nationalists in the magazine "Szczerbiec". Serbian topics in Polish nationalist communities can count on special interest and recognition. The nationalist environments of many countries are showing solidarity with the Serbian nation in Kosovo and demanding recognition of their rights to these lands. e sympathy shown by Serbs to Poles, whose Slavic origins are linked, is pointed out. It can be assumed that the characteristics, attitude and views of the Serbs will foster mutual relations in the future.
Keywords: Serbs; nationalists; Kosovo; Narodowe Odrodzenie Polski; Serbowie; nacjonaliści; Kosowo